Technology Intergration in Teaching, Student Motivation, and Reading Achievement - sedimo, N. Losike; Ngwako, A. (Advances in Social Sciences Research Journal, 2016)
The study investigated technology integration impact on students’ reading achievement, student motivation, and teacher proficiency in technology integration. The objective of the study was to find ways to improve students’ classroom experiences in order to foster learning. The focus was on improving students’ reading scores. The importance of the study was that reading exam scores together with all other subjects were declining in selected community junior secondary school. Using the theory of experiential learning, we designed the single group pretest and posttest study. Three research questions were formulated and investigated. Data were collected from four junior secondary schools, two in Lobatse City and two in the city of Gaborone. A sample of 140 students was pretested and post tested for reading achievement and motivation after been exposed to the Interactive board technology teaching. (SMART board technology). Four teachers for the four classes were also pretested and post tested for proficiency after been trained. Data were analyzed using SPSS. Results showed that the integration of technology in the method of teaching improved, reading scores, motivation and teacher proficiency. Keywords Reading achievement, blended e - learning, experiential learning and motivation